CHARACTERISTICS OF SLIP POWER, ANTIOXIDANT POTENTIAL, AND ORGANOLEPTIC PROPERTIES OF PINEAPPLE JAM WITH THE ADDITION OF PECTIN AND AGAR-AGAR THICKENERS - Nadhilah, Dini; Rochmah, Alfi Nur; Abdi, Yenny Febriana Ramadhan; Riski, Prajwalita Rukmakharisma; Suleman, Dininurilmi Putri; Zulfa, Fitriyah; Aprilia, Intan Dwi; Aprilia, Wulan (Universitas Veteran Bangun Nusantara, 2025)
Pineapple jam is a processed fruit product that is popular among various groups of people because of its distinctive sweet and sour taste and chewy texture. The process of making pineapple jam involves several important stages, starting from selecting and preparing the raw materials, namely ripe pineapples. After that, the pineapple is grated or crushed, then cooked with sugar and other additional ingredients such as pectin, citric acid and preservatives. The cooking process is carried out by heating gradually to evaporate some of the water and thicken the jam. This process also aims to activate pectin which functions as a natural thickening agent. After reaching the desired consistency, the pineapple jam is cooled, then packaged in sterile containers to maintain the quality and durability of the product. Important parameters in the process of making pineapple jam include water content, sugar content and pH, which affect the quality and shelf life of the product. The final results of this research show that the correct use of pectin and citric acid can produce pineapple jam with optimal texture and delicious taste, and has a long shelf life if stored properly. Keywords: Citric acid; jam; pineapple; pectin; texture.